Utilization, Simulation and Learning: The Virtual Laboratory Learning Media PhET for Outcomes Learning - Warneri, Warneri; Salam, Urai; Putri, Wicha Amalia; Imandari, Ratih Zatil; Pratiwi, Rani Diah; Chairunnisa, Tara (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study examines the effectiveness of PhET simulations in improving physics learning outcomes for Class XII IPS 4 students at SMA Negeri 1 Beduai. Physics is often perceived as a challenging subject due to its abstract concepts, which are difficult to visualize and understand using traditional teaching methods. Interactive digital tools like PhET simulations offer a promising approach to help students grasp complex concepts more easily. Using a quasi-experimental design, the study compares an experimental group, which used PhET simulations, with a control group that followed traditional teaching methods. The study analyzed pre-test and post-test scores to assess the impact of the simulations on student learning. The results show a significant improvement in the experimental group's performance, with post-test scores noticeably higher than pre-test scores. Statistical analysis, including paired sample t-tests, confirmed that PhET simulations significantly enhanced students' problem-solving skills and understanding of physics concepts (t = -17.329, p < 0.05). These findings highlight the effectiveness of PhET simulations, combined with an inquiry-based learning approach, in fostering a deeper understanding of abstract physics concepts and promoting critical thinking. Overall, this study supports the use of PhET simulations as a practical and accessible tool for improving physics education, even in schools with limited technological resources.